Displacements recorded on continuous GPS stations following the 2014 M6 Cephalonia (Greece) earthquakes: Dynamic characteristics and kinematic implications - Athanassios Ganas; F. Cannavo; K. Chousianitis; Kassaras, I.; Drakatos, G. (Acta Geodynamica et Geomaterialia, 2015)
We report cm-size dynamic displacements of continuous GPS stations onshore the island of Cephalonia, Ionian Sea, Greece, following the passage of seismic waves from two (2) shallow earthquakes on Jan 26, 2014 and Feb 3, 2014, respectively. First, we estimated the displacements from the high-rate GPS data collected at NOA station VLSM, near to the epicenters, by using state-of-art data processing strategies. The time series of displacements were analyzed both in time and frequency domains. From the dynamic analysis of 1Hz data it is shown that the second event was recorded at station VLSM with higher amplitudes on both horizontal components, despite its smaller (22 %) moment magnitude, possibly due to its shallower depth. The static field of deformation is characterized by cm-size permanent motion in opposing directions between stations KIPO (western Cephalonia) and VLSM (eastern Cephalonia), in agreement with the right-lateral kinematics of both ruptures. The 7.4 cm northward motion of station KIPO implies that the western peninsula of Cephalonia island (Paliki) belongs to a separate crustal block with respect to the rest of the island. The northward motion of KIPO also implies that the Cephalonia Transform Fault (CTF) did not rupture during the 2014 events, because KIPO is located at the hanging wall of CTF. It is possible that the amount of accumulated strain along CTF since 1983 (M=6.8) can be released by a seismic event of M6.5-6.7, at any time.